2019
DOI: 10.37358/rc.19.9.7526
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity Exerted by Total Extracts of Germander

Abstract: In the present research, ethanolic and methanolic extracts of Teucrium polium (germander) were studied regarding the content of biologically active substances - in particular polyphenols - antioxidant activity and antibacterial activity. The extracts have been found to be rich in polyphenolic compounds, kaempferol and epichatechin have been found to be present in the highest concentrations. The antioxidant activity evaluated by the method of capturing the free radicals with DPPH revealed values close to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, the hydrophilic/lipophilic character of the used solvents (diethyl ether, ethyl acetate and n-butanol) is different from ours (methanol, methanol/dichloromethane) which enabled also the extraction of the glycosides. Preliminary studies on Tunisian T. polium showed that the methanolic extract was richer in flavonoids and polyphenolic acids than the ethanolic extract [3]. Various iridoid glycosides were identified in Italian T. chamaedrys, but harpagide (for which we used HPLC grade standard) was detected only in T. polium and T. montanum samples [11].…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…However, the hydrophilic/lipophilic character of the used solvents (diethyl ether, ethyl acetate and n-butanol) is different from ours (methanol, methanol/dichloromethane) which enabled also the extraction of the glycosides. Preliminary studies on Tunisian T. polium showed that the methanolic extract was richer in flavonoids and polyphenolic acids than the ethanolic extract [3]. Various iridoid glycosides were identified in Italian T. chamaedrys, but harpagide (for which we used HPLC grade standard) was detected only in T. polium and T. montanum samples [11].…”
Section: Resultsmentioning
confidence: 92%
“…Higher amounts of rosmarinic acid, caffeic acid and cinnamic acid were also identified. Similar compounds were identified in Teucrium chamaedrys from Serbia, Italy and Romania, T. polium from Iran, Tunisia and T. montanum from Serbia [1,3,11,14,18,20,[22][23][24][25]. In a comprehensive study, Panovska et al evaluated the chemical profile of three Macedonian endemic Teucrium species (T. chamaedrys, T. polium and T. montanum) [20].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One of the areas in which natural compounds find their utility is the treatment of bacterial infections, given that modern medicine is currently facing a crisis of increasing resistance to conventional antibiotics [13]. In terms of composition, plants have over 2000 compounds that can be classified according to their chemical structure into four major groups: terpenoids, nitrogen compounds, sulfur compounds, and phenolic compounds [14,15].…”
Section: Vegetal Sources Of Compounds On Dentistry Productsmentioning
confidence: 99%